PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN LITERASI KEAGAMAAN SISWA (Studi Kasus di Sekolah Menengah Pertama Takhassus Al-Qur’an Kalibeber, Wonosobo) - Kholifatun Khasanah; Moh. Sakir; Maryono Maryono (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The low level of religious literacy among students poses a challenge in Islamic education, particularly in shaping religious character. Islamic Education teachers play an important role in instilling values and guiding students to comprehensively understand and practice the teachings of Islam. This study aims to examine the role and strategies of Islamic Education teachers in enhancing students' religious literacy at SMP Takhassus Al-Qur'an Kalibeber, Wonosobo. The method used is qualitative descriptive with data collection through observation, interviews, and documentation. Data analysis is conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results show that teachers function as educators, guides, facilitators, and role models. The main strategies implemented include reading the classical book Al-Ibriz every morning, habituation of worship, contextual learning, and the implementation of as well as the utilization of school libraries. Supporting factors include the religious culture in schools and pesantren programs, while inhibiting factors include the limited reading materials and the low interest in reading among students.